2006
DOI: 10.4321/s0004-06142006000500006
|View full text |Cite
|
Sign up to set email alerts
|

Tratamiento endoscópico del reflujo de vesicoureteral en pediatría: Experiencia preliminar con la inyección subureteral de coaptite®

Abstract: Resumen.-OBJETIVO: Analizar nuestra experiencia en el tratamiento endoscópico del reflujo vesicoureteral (RVU) en pediatría, mediante la inyección subureteral de hidroxiapatita cálcica (Coaptite®

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The primary center success rate reported by Mevorach et al is similar to the European single-center studies of CaHA, which have shown 70–80% success rates after two injections [8, 10, 11]. …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The primary center success rate reported by Mevorach et al is similar to the European single-center studies of CaHA, which have shown 70–80% success rates after two injections [8, 10, 11]. …”
Section: Discussionsupporting
confidence: 75%
“…Multiple authors have described a significant frequency of late failures regardless of whether Dx/HA or CaHA was used [11, 1315]. Most of these studies showed failures at 1 year but not much further beyond that.…”
Section: Discussionmentioning
confidence: 99%